2014
DOI: 10.1007/s12185-014-1578-y
|View full text |Cite
|
Sign up to set email alerts
|

Experience from a single paediatric transplant centre with identification of some protective and risk factors concerning the development of hepatic veno-occlusive disease in children after allogeneic hematopoietic stem cell transplant

Abstract: Hepatic veno-occlusive disease (VOD) is a frequent and severe complication of hematopoietic stem cell transplantation (HSCT) affecting 9.6-17.3 % of cases. 200 HSCT, performed between January 1995 and March 2013 in our Paediatric HSCT Centre in Trieste, were retrospectively analysed to evaluate the frequency of VOD and to identify the associated risk factors. The frequency of VOD according to the Seattle criteria was 17 %, within the range reported in literature. The mortality rate was 37.5 % (75 out of 200 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…Studies that evaluated risk factors for VOD/SOS in large HSCT recipient populations over the past 5 to 7 years vary in consistency with previous data and reveal potential risk factors that have not previously been noted [21,23,26,[36][37][38][39] (Table 5). Among 10 such studies identified for this review, with total numbers ranging from 75 to 5072 patients, incidence of VOD/ SOS ranged from 2.0% (lowest incidence was diagnosed with EBMT criteria) to 30.7% (Table 5).…”
Section: Recent Studies Of Risk Factors For Vod/sos In Hsct Recipientsmentioning
confidence: 57%
See 2 more Smart Citations
“…Studies that evaluated risk factors for VOD/SOS in large HSCT recipient populations over the past 5 to 7 years vary in consistency with previous data and reveal potential risk factors that have not previously been noted [21,23,26,[36][37][38][39] (Table 5). Among 10 such studies identified for this review, with total numbers ranging from 75 to 5072 patients, incidence of VOD/ SOS ranged from 2.0% (lowest incidence was diagnosed with EBMT criteria) to 30.7% (Table 5).…”
Section: Recent Studies Of Risk Factors For Vod/sos In Hsct Recipientsmentioning
confidence: 57%
“…Risk factors for VOD/SOS identified in these studies following univariate, but not multivariate, analysis included cyclophosphamide in an adult study [37] and previous radiation therapy in adults (but not in children in the same study) with high-risk Ewing sarcoma [40]. Transplantation-related factors that reduced the risk of VOD/SOS were reported in 2 pediatric studies [30,39]. These included the use of tacrolimus instead of cyclosporine as a prophylaxis for graft-versus-host disease [39] and the use of cord blood cells as a stem cell source, although this source was used in only 6% of patients in the study [30].…”
Section: Recent Studies Of Risk Factors For Vod/sos In Hsct Recipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different observational period of the two groups and the constantly increasing amelioration in diagnostic and therapeutic management may explain this result. However, none of the patients in the DG cohort manifested VOD, even though the incidence of this disease was near 8% in our population [11]. Values are given as n (%) ARI acute renal insufficiency, BMT bone marrow transplantation, MOF multiorgan failure, VOD venoocclusive disease…”
Section: Discussionmentioning
confidence: 68%
“…Defibrotide (DF) has been used for preventing VOD in children. It was reported that DF could significantly reduce the incidence of VOD in pediatric patients undergoing HSCT [20,21]. However, no randomized prospective study evaluating VOD prevention with DF has so far been reported in adult patients.…”
Section: Discussionmentioning
confidence: 99%